Glutathione as a Biomarker in Parkinson's Disease: Associations with Aging and Disease Severity. (30th June 2016) - Mischley, Laurie K.; Standish, Leanna J.; Weiss, Noel S.; Padowski, Jeannie M.; Kavanagh, Terrance J.; White, Collin C.; Rosenfeld, Michael E.
Abstract : Objectives . Oxidative stress contributes to Parkinson's disease (PD) pathophysiology and progression. The objective was to describe central and peripheral metabolites of redox metabolism and to describe correlations between glutathione (Glu) status, age, and disease severity. Methods . 58 otherwise healthy individuals with PD were examined during a single study visit. Descriptive statistics and scatterplots were used to evaluate normality and distribution of this cross-sectional sample. Blood tests and magnetic resonance spectroscopy (MRS) were used to collect biologic data. Spearman's rank-order correlation coefficients were used to evaluate the strength and direction of the association. The Unified PD Rating Scale (UPDRS) and the Patient-Reported Outcomes in PD (PRO-PD) were used to rate disease severity using regression analysis. Results . Blood measures of Glu decreased with age, although there was no age-related decline in MRS Glu. The lower the blood Glu concentration, the more severe the UPDRS (P = 0.02, 95% CI: −13.96, −1.14) and the PRO-PD (P = 0.01, 95% CI: −0.83, −0.11) scores. Discussion . These data suggest whole blood Glu may have utility as a biomarker in PD. Future studies should evaluate whether it is a modifiable risk factor for PD progression and whether Glu fortification improves PD outcomes.